2018
DOI: 10.1016/j.oret.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Intraoperative OCT–Assisted Epiretinal Membrane Surgery from the PIONEER Study

Abstract: OCT-assisted ERM peeling resulted in significant improvement in visual acuity, reduction in macular thickness, and low recurrence rate. Additional research is needed with randomized clinical trials to better define the comparative success rates of image-guided ERM surgery to standard surgical visualization techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 30 publications
1
17
0
1
Order By: Relevance
“…Recently, microarchitectural changes after peeling, diagnosed with iOCT imaging after peeling compared to iOCT images before peeling, have been reported. Distances between the ellipsoid zone and retinal pigment epithelium, as well as between the cone outer segment tips/ interdigitation zone and retinal pigment epithelium, were significantly increased after peeling [13]. These changes indicate that traction-induced changes in retinal tissue occur during membrane peeling, even in cases without subfoveal/extrafoveal hyporeflective zones.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, microarchitectural changes after peeling, diagnosed with iOCT imaging after peeling compared to iOCT images before peeling, have been reported. Distances between the ellipsoid zone and retinal pigment epithelium, as well as between the cone outer segment tips/ interdigitation zone and retinal pigment epithelium, were significantly increased after peeling [13]. These changes indicate that traction-induced changes in retinal tissue occur during membrane peeling, even in cases without subfoveal/extrafoveal hyporeflective zones.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, some of the evidences also emphasize the reduced need for unintended surgical maneuvering with iOCT in the vicinity. 74 , 75 , 86 In an observation by Falkner-Radler et al, 87 in 40% of the cases dye was not necessary to peel the ERM, and, in around 95% of the cases iOCT ascertained its completeness with clear revelations on underlying traumatic changes if at all. 88 In another observation, 63% of the eyes were peeled off ERM without the use of dye, 89 hence, the 4D technology with volumetric information in real time can circumvent the need for dyes as well.…”
Section: Resultsmentioning
confidence: 98%
“…For posterior segment surgery, iOCT appears to be particularly useful during membrane assessment, such as in PDR and ERM surgery. 25, 26 A recent prospective study utilizing microscope-integrated iOCT during membrane peeling procedures confirmed the ability of the technology to enhance visualization of the underlying membranes and subtle post-peel architecture changes. 15 An additional study recently reported membrane peeling with iOCT feedback was able to performed without the use of adjuvant dyes through the identification of membrane edges with the OCT system.…”
Section: Discussionmentioning
confidence: 78%